A Calorimetric Characterization of Cr(VI)-Reducing Arthrobacter oxydans at Different Phases of the Cell Growth Cycle. (2003) - Bakradze, Nugzar G.; Abuladze, Marina K.; Sokhadze, Victor M.; Asatiani, Nina V.; Sapojnikova, Nelly A.; Kartvelishvili, Tamara M.; Namchevadze, Emma N.; Tsibakhashvili, Nelly Y.; Tabatadze, Leila V.; Lejava, Lia V.; Holman, Hoi-Ying
Abstract : This is the first of a series of calorimetric studies designed to characterize and understand survival mechanisms of metal-reducing bacteria isolated from metal-polluted environments. In this paper we introduce a new concept of thermal spectrum of the endothermic melting of complex biological systems (e.g., proteins, nucleic acids, ribosomes, membrane structures) in intact cells. All thermal spectra measured are thermograms that describe the temperature dependence of heat capacity change of the complex systems of biologically active substances in bacterial cells . This new concept of thermal spectrum was applied to investigate spectral features from intact cells of Cr(VI)-reducer Arthrobacter oxydans at different points of their growth conditions and stages. Over the temperature range of 40–105 ° C, we observed that spectral changes are particularly significant in the 40–90 ° C interval. This may correspond to the orderly changes in subcellular structural elements: proteins, ribosomes and RNA, membranes, and various structural elements of the cell wall during different points of the growth cycle and growth conditions. Spectral changes in the 90–105 ° C region are less pronounced, implicating that the structural composition of DNA-Protein (DNP) complexes may change little.